EXPERIENCE WITH DOLUTEGRAVIR IN HIV PATIENTS AT A PUBLIC SECTOR HOSPITAL IN KARACHI, PAKISTAN: Dolutegravir in HIV - Batool, Farzana; Manzoor, Sohaima; Dhiloo, Azizullah Khan; Ismail, Humera Muhammad; Shaikh, Shah Muhammad; Baqi, Shehla (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study the tolerability and efficacy of dolutegravir in naïve and experienced patients, their management and outcome. Study Design: Cross sectional study. Place and Duration of Study: Ruth KM Pfau Civil Hospital, Karachi Pakistan, from Apr 2018 to Apr 2020. Methodology: In this study all treatment-naïve and experienced HIV infected patients were included and started on integrase strand-transfer inhibitor dolutegravir (DTG) containing fixed dose combination at Sindh AIDS Control Program (SACP) was conducted. We documented virological suppression, defined as a viral load of <1000 copies/ml, immunological and clinical outcomes. Results: Eighty-two patients, of whom 53 (64.6%) were ARV naïve and 29 (35.4%) experienced, were started on DTG. Fifty six (68.3%) were males. The median age was 31.6 ± 9. Of 82, 61 returned for their first follow-up visit for assessment and viral load determination. Of 61, adverse effects to DTG were reported in 12 (19.6%), including 9 with pruritis. Of 35 naive patients, 30 achieved virological suppression by 3.3 ± 0.7 months and 1 at 8 months. All 26 experienced patients achieved virological suppression by 4.5 ± 0.9 months. Overall, of 61 patients, 57 (93.4%) achieved virological suppression, of whom 1 had immunelogical failure and none had clinical failure after 6 months of DTG. Three (3.6%) patients died within the first two months of initiating DTG. Conclusion: Dolutegravir has good tolerability, with virological suppression achieved in the majority, including in highly ARV experienced patients.